ANALISIS DAYA SAING PEDAGANG ASLI PAPUA DI PASAR SENTRAL TIMIKA - Novi Irianti Tanassy; Tharsisius Pabendon (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2019)
This study aims to find out how the competitiveness work ini native Papuan traders of Timika Central Market, and identify factors constraining in the competitiveness. The research using descriptive research methodto describe the object. Data collection using observation and questionnaire. Chi Square analysis (X2)occupied to analyze the competitiveness of native Papuan traders and the factors constraining one sampel. The results showed that competitiveness of native Papuan traders were hindered by five factors. Namely lack of goods competence, less attractive arrangement of selling goods, low quality of goods, prices of goods that are less competitive and inadequate shopping facilities.